OPTIMIZING JULUNG-JULUNG (Hemiramphus sp.) FISHERY USING SURPLUS PRODUCTION MODELS iN EAST SERAM - Stany Rachel Siahanenia; Agustinus Tupamahu; Halik Litiloli (Bogor Agricultural University, 2025)
The julung-julung (Hemiramphus sp.) fishery in eastern Seram waters is an important livelihood resource for coastal communities, yet it is increasingly exposed to high exploitation pressure driven by intensified fishing and coastal habitat degradation. This study assesses the stock status and identifies optimal management strategies using a surplus production modelling approach. Catch (tons) and fishing effort (number of trips) data from 2014–2024 were analyzed using the Schaefer and Fox models. Model comparison showed that the Fox model provided a better fit to the observed data, with an R² of 76.0%, compared with 73.3% for the Schaefer model. Based on the Fox model, the estimated maximum sustainable yield (MSY) was 945.7 tons per year, with an optimal fishing effort (Eopt) of 2,365 trips per year. The declining trend in catch per unit effort (CPUE), despite continued increases in fishing effort, indicates reduced fishing efficiency and suggests that the stock is already experiencing overfishing. These results demonstrate that the julung-julung fishery in eastern Seram waters is under overexploitation and requires urgent management intervention. Effort regulation aligned with Eopt, together with ecosystem-based and participatory management approaches, is recommended to support recovery and long-term sustainability. The findings provide evidence-based guidance for strengthening policy development and management of small-scale, data-limited tropical fisheries, particularly those facing similar ecological and socioeconomic pressures. Keywords: Hemiramphus sp., MSY, CPUE, Fox model, fisheries management